Small-for-gestational-age babies of low-risk term pregnancies: does antenatal detection matter?. (3rd June 2018) - Policiano, Catarina; Fonseca, Andreia; Mendes, Jorge M.; Clode, Nuno; Graça, Luís M.
Abstract: Objectives: To compare delivery route and admission rate to neonatal intensive care unit between small- and appropriate-for-gestational-age babies among low-risk term pregnancies. Methods: A retrospective study was conducted using the database of deliveries in 2014 at a tertiary hospital. Babies delivered at ≥37 weeks with birthweight <10th centile were considered small-for-gestational-age (SGA) and >90th centile were considered large-for-gestational-age. Fetal weight estimation at 30–33 weeks ultrasound <10th centile was considered antenatal detection of SGA. Results: Among 1429 low-risk term pregnancies, 11% (151/1429) had SGA babies and 5% (75/1429) had large-for-gestational-age. SGA babies were associated with higher rate of cesarean sections for nonreassuring fetal status (18/151 versus 8/1202, p < .001) and higher rate of admissions to neonatal intensive care unit (16/151 versus 18/1202, p < .001) compared to appropriate-for-gestational-age. Within SGA group, antepartum detected fetuses were associated with lower rate of operative deliveries for nonreassuring fetal status than undetected group (3/31 versus 39/120, p = .01) Conclusions: In our series, women with SGA term babies were associated with more adverse obstetric and neonatal outcome than appropriate-for-gestational age, especially among those undetected prenatally.